The role of the printed agricultural press in disseminating agricultural knowledge among farmers of the Shahat region (A case study in the Shahat area in Jabal Al Akhdar) (Faculty of Education Scientific Journal, 2024)
Agricultural extension science is concerned with the process of disseminating and communicating new agricultural information to farmers, and since this process is very important and part of the science of agricultural extension, so communication with farmers is considered one of the pillars of extension science. Agricultural extension faces many criticisms in communicating agricultural information and technical recommendations to farmers through means of communication. The traditional agricultural press and publications of all kinds were chosen. A research sample of (42) respondents was selected, representing 40% of the overall total of 105 farmers. Among the most important findings of the research was that farmers’ attitudes towards obtaining printed agricultural press were weak, and that farmers’ exposure to information sources Agriculture was weak and this may be due to the absence of publishing houses Technical guidance and the lack of issues issued by Al-falah magazine, all of which are important sources of agricultural information in disseminating agricultural knowledge to the respondents in the research sample. It was found that farmers’ benefit from agricultural information sources was weak and this may be due to the lack of periodic follow-up by agricultural extension workers to the technical guidance issued by the authorities responsible for production. Agricultural, both plant and animal, and it became clear that there is a deficiency in the timely arrival of the printed agricultural press. This may be due to the weakness of the budget allocated for that, or the small number of them issued, in addition to the reluctance of the respondents to follow it. It was found that there is no correlation between the independent variables and benefiting from the role of The printed agricultural press in disseminating agricultural knowledge in the research sample.
Keywords: Agricultural press; agricultural knowledge; agricultural bulletin; periodical letters; extension publications